Elastic Characteristic Extraction Method of Underwater Target Based on Adaptive Filtering - Zhen-Shan Wang; Yun-Fei Chen; Gui-Juan Li; Ji-Hui Wang (电子科技学刊, 2012)
TN912.3; In this paper,a kind of elastic characteristic extraction method of underwater targets based on adaptive filtering is introduced.The kernel of the method is the recursive least square (RLS) algorithm.Firstly,the geometric scattering signal is fit by using the echo signal and the incident signal.Then,the frequency spectrum of the echo signal and the geometric scattering signal are calculated.At last,the frequency spectrum of the elastic scattering signal is obtained.The research of the simulation and lake experiment is carried on.As the results show,the formants of the elastic signal frequency spectrum can be precisely extracted by the algorithm,and the extraction algorithm can apply to extracting the elastic characteristic from the echo signal in a real underwater acoustics environment.